HUBUNGAN ASUPAN ZAT BESI DAN INHIBITORNYA SEBAGAI PREDIKTOR KADAR HEMOGLOBIN IBU HAMIL DI KABUPATEN MUARA ENIM - Jhon Riswanda (Biota, 2017)
The prevalence of anemia in pregnant women is still high (69,7%). Low iron intake and high intake of iron inhibitors may have a role to the anemia prevalence in pregnant women. However, the contibution of iron inhibitors on anemia prevalence is still unknown. Objective : The study was conducted to investigate the relationship between intakes of iron inhibitors and hemoglobin level of pregnant women. Methods: This cross sectional study was conducted in Muara Enim regency. Subjects of this study were 244 pregnant women with 20-28th weeks of gestation. Iron and iron-inhibitor intake were collected by trained interviewers using food frequency questionnaires. Socioeconomic data were also collected using structured questionnaires. Hemoglobin concentration of pregnant women was measured by using cyamet henoglobin method at the start of the study. Data analysis was done using STATA sofware. Result: About thirty seven present (37,29%) of pregnant women in this population were anemic. In multiple linear regression models, intake of iron, calcium and tannin were significantly associated with hemoglobin concentration ( p< 0,05). Every 1 mg of iron intake was associated with 0,052 gr/dl increase in Hemoglobin concentration. On the other hand, every 1 mg of calcium intake and every 1 gr of tannin intake were associated with 0,00687 gr/dl and 0,123 gr/dl decrease in hemoglobin concentration. Pregnant women with a high iron intake have a higher hemoglobin concentration. In contrast, pregnant women with a high intake of tannin and calcium have a lower hemoglobin concentration.